PENGETAHUAN DAN TINGKAT KONSUMSI ZAT GIZI DENGAN STATUS GIZI SMAN 1 DAWAN KABUPATEN KLUNGKUNG - K. Pitaloka Cahyani; Ni Made Yuni Gumala; Pande Putu Sri Sugiani (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
The cause of the emergence of nutritional problems is nutrition knowledge that affects the level of consumption of nutrients. The purpose of this study was to determine the relationship between knowledge of nutrition and the level of consumption of macro nutrients with nutritional status of students at SMAN 1 Dawan, Klungkung Regency. This type of observational research was designed with sperman correlation and the number of samples was 88. Data was collected by interview method and anthropometric measurements. Data analysis using spearman correlation test. The results showed that most nutrition knowledge (65,91%) was sufficient. Most levels of energy consumption are severe deficits (92%). As much as (67,05%) the level of consumption of heavy protein deficits. The level of fat consumption is mostly (88,64%). The level of carbohydrate consumption is mostly (81,85%) heavy deficit. Most nutritional status (69,32%) is normal. The results showed that there was no significant relationship between knowledge of nutrition and nutritional status. There is a significant relationship between the level of consumption of macro nutrients (energy, protein, fat, carbohydrate) and nutritional status.